Transmedia Storytelling and the Evolution of Popular Narrative in the Age of Social Media - Webster, Luke (Curtin University, 2024)
Drawing on case studies from the Marvel, DC and Star Wars franchises and interviews with leading entertainment industry practitioners, this research interrogates the various approaches to commercial transmedia storytelling from 2008 to 2021 and the increasing popularity of collective journey storytelling. It concludes that when commercial storytellers treat transmedia storytelling as a flow of cultural energy rather than simply a commercial practice, it can achieve better commercial outcomes and affect social change.